Effectiveness of Telementoring in Surgery Compared With On-site Mentoring: A Systematic Review. (August 2017) - Bilgic, Elif; Turkdogan, Sena; Watanabe, Yusuke; Madani, Amin; Landry, Tara; Lavigne, Daniel; Feldman, Liane S.; Vassiliou, Melina C.
Background. Mentorship is important but may not be feasible for distance learning. To bridge this gap, telementoring has emerged. The purpose of this systematic review was to evaluate the effectiveness of telementoring compared with on-site mentoring. Methods. A search was done up to March 2015. Studies were included if they used telementoring between surgeons during a clinical encounter and if they compared on-site mentoring and telementoring. Results. A total of 11 studies were included. All reported no difference in complication rates, and 9 (82%) reported similar operative times; 4 (36%) reported technical issues, which was 3% of the total number of cases in the 11 studies. No study reported on higher levels of evidence for effectiveness of telementoring as an educational intervention. Conclusion. Studies reported that telementoring is associated with similar complication rates and operative times compared with on-site mentoring. However, the level of evidence to support the effectiveness of telementoring as a training tool is limited. There is a need for studies that provide evidence for the equivalence of the effectiveness of telementoring as an educational intervention in comparison with on-site mentoring.